Hubungan Smoking Media Literacy dengan Status Merokok Siswa Menengah Atas - Ayubi, Dian; Martha, Evi; Sugiarto, Danang Wahansa (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2020)
Background. Media exposure is a very influential factor in the initiation of adolescents to smoke. Therefore, media literacy (smoking media literacy [SML]) was developed as a school-based tobacco control strategy. Objective. The purpose of this research was to examine the relation of SML with the smoking status of high school students in Purwakarta Regency Method. This research used quantitative research with a cross-sectional design conducted in April-May 2018 in Purwakarta Regency. Data were collected by self-administered questionnaires from 310 students of public senior high school. Data were analyzed using logistic regression test. Statistical adjustments were made for gender, parental education, parenting, smoking status of parents, siblings, and peers, school performance, depression, self-esteem, rebellion, and sensation seeking character. Results. There were 14.2% smokers among respondents. The mean of SML score was 68.94 (on a scale of 100). The result of logistic regression showed that there was a significant correlation between SML and smoking status with adjustment by sex, the sibling who smokes, peers who smoke, school achievement, and rebelliousness (p-value=0.048; CI=1.008-7.085). Conclusions. High school students' understanding of media literacy was still low, and SML was related to students' smoking status.